DISCLOSURE EKUITAS MEREK DALAM LAPORAN PERUSAHAAN - K. Bagus Wardianto (P3M STISIPOL Dharma Wacana Metro, 2018)
This paper aims to provide an overview of the disclosure of brand equity in annual reports and corporate finance. This paper also aims to provide input to the Financial Services Authority (OJK) and the Financial Accounting Standards Board regarding the disclosure of brand equity in annual reports and corporate finance. This paper is written using a deep literature review and is followed by the presentation of descriptive data related to the calculation of brand equity. Considering the importance of brand equity for company management and investors, through this paper it is deemed necessary to advise OJK, the Financial Accounting Standards Board regarding disclosure of brand equity in annual reports and company finances.